A method of verifying the statistical performance of electronic circuits designed to analyze the power quality. (November 2016) - Hernandez, Wilmar; Calderón-Córdova, Carlos; Brito, Eduardo; Campoverde, Eduardo; González-Posada, Vicente; Zato, José G.
Highlights: A method of verifying the performance of a power quality analyzer is proposed. The method relies on the Wilcoxon signed-rank test and the Levene test. The method is independent on the distribution of the electrical signals. The method compares statistically a prototype circuit with a reference instrument. The performance of a prototype of a power quality analyzer has been verified. Abstract: The main contribution of this paper is that a novel method of verification of the statistical performance of electronic circuits that have been specifically designed to analyze the power quality is proposed. The method is based on the Wilcoxon signed-rank test and on the Levene test, which are nonparametric statistical inference techniques, and it establishes the relation that exists between the measurement results obtained using a reference instrument and the measurement results obtained using the electronic circuit under test. In addition, the method says whether the performance of the device under test differs significantly from what would be expected. Finally, in order to show the feasibility of the proposed method, a prototype circuit was designed and a practical application of the method is shown. The main idea of the proposed method can also be used to analyze the performance of a wide range of circuits used in different industrial applications.